Nanocomposites with polyurethane polymer matrix/ particulate material (International Seven Journal of Multidisciplinary, 2024)
The environment is currently considered one of the main concerns of the industrial sector and society. In the particular case of the oil industry, one of the biggest environmental catastrophes that can happen are large oil spills, where to reduce or minimize the environmental damage caused, various cleaning methods are used. Thus, nanocomposites aim to change the mechanical, physical and chemical properties of polymer matrices. The main focus of modifying Polyurethanes has been directed to materials science, the objective of which is to obtain particulate materials, allowing surfaces to be differentiated, reducing surface energy and increasing interlayer spacing for polymer intercalation. This particulate material, produced and modified, interspersed with the Polymer, allows us to absorb crude oil, as it is hydrophobic and, consequently, organophilic. The factors that define the degree of sorption of organic compounds are: hydrophobicity, porosity, molecular structure and volume, and the volume of the surface area of the sorbent material. Therefore, the sorbent must be wettable by the hydrophobic compound and non-wettable or slightly wettable by water. Sorbent materials must have characteristics such as a large surface area, high porosity, good oleophilic character, as well as good oil retention capacity and ease of application. Polyurethane presents several of these characteristics, making it an interesting sorbent for the oil sector. The present work studies the obtaining of these nanocomposites, using a particulate material to combat leaks or spills of hydrocarbons.